One-step eco-friendly approach for the fabrication of synergistically engineered fluorescent copper nanoclusters: sensing of Hg2+ ion and cellular uptake and bioimaging properties. (4th January 2018) - Bhamore, Jigna R.; Deshmukh, Balaji; Haran, Varun; Jha, Sanjay; Singhal, Rakesh Kumar; Lenka, Nibedita; Kailasa, Suresh Kumar; Murthy, Z. V. P.
Abstract : Schematic illustration for one-step green synthetic approach for fabrication of synergistically engineered CuNCs. Abstract : Herein, a single-step eco-friendly synthetic method was established for the fabrication of synergistically engineered fluorescent copper nanoclusters (Cu NCs) using curcuma root ( Curcuma longa L.) extract (curcuminoids) as a template. These Cu NCs are water-soluble and emitted bright blue fluorescence under UV light illumination at 365 nm. The synergistically engineered Cu NCs exhibited an emission peak at 440 nm with quantum yield of 7.2%. Due to their optical properties, a new fluorescent analytical strategy has been developed for the sensing of Hg 2+ ions and used to evaluate cellular uptake and bioimaging properties on cancer cells (RIN-5F and MDAMB231) and fungal cells ( Penicillium citrinum ). It was interestingly observed that Hg 2+ ion effectively quenched the emission peak of Cu NCs at 440 nm, which indicates that Cu NCs act as a fluorescent sensor. Taking advantage of this, a novel fluorescent Hg 2+ sensor has been established, which showed a linear range of 0.0005–25 μM with a detection limit of 0.12 nM at room temperature. Furthermore, Cu NCs exhibited good selectivity for Hg 2+ against other inorganic species, and the potentiality of the method was demonstrated by detecting Hg 2+ ions in water samples. Furthermore, Cu NCs act as probes for imaging of two cancer cells (RIN-5F and MDAMB231) and fungal cells ( Penicillium citrinum ), and the cell viability results reveals their nontoxic nature.